Peranan Manajemen Risiko dan Kecukupan Permodalan terhadap Kinerja Keuangan Perbankan Umum Konvensional Tbk Tahun 2018-2022 - Ramadhan, Muhammad Alriansyah; Suhartini, Dwi (Al-Buhuts, 2024)
This research aims to examine the influence of Risk Management and Capital Adequacy on the Financial Performance of Conventional General Banking listed on the Indonesia Stock Exchange in the 2018-2022 period. There were 24 samples of banking companies taken using the Purposive Sampling method with criteria determined by researchers to support this research. This research uses quantitative methods with secondary data from annual reports of banking companies obtained from the websites of the Indonesian Stock Exchange, Financial Services Authority, and Conventional General Banking companies included in this research sample. This research uses Multiple Regression Analysis with the SPSS version 25 application. Independent variables include Risk Management (measured by NPL, NIM, LDR, BOPO) and Capital Adequacy (measured by CAR). The dependent variable is Financial Performance (measured by ROA). Data was collected using the Literature Study and Documentation method to make data collection easier. The research results show that NPL and BOPO have a negative effect, NIM has a positive effect, and LDR and CAR have no effect on ROA